Carbide derived carbons investigated by small angle X-ray scattering: Inner surface and porosity vs. graphitization. (May 2019) - Härk, Eneli; Petzold, Albrecht; Goerigk, Günter; Risse, Sebastian; Tallo, Indrek; Härmas, Riinu; Lust, Enn; Ballauff, Matthias
Abstract: Small angle X-ray scattering (SAXS) was used to study the nanostructure of Mo2 C derived carbon powders (CDC) synthesized at five different chlorination temperatures. The SAXS-intensities have two contributions: i) a fluctuation contribution from small partially graphitized areas that gives quantitative information about the extent of graphitization, and ii) the scattering from the pores. The fluctuation contribution that scales with q −2 was quantified in term of a length parameter l R and a disorder parameter that can directly be correlated with the increasing graphitization with increasing temperature. The specific inner surface area of the CDC together with the volume fraction ϕ of the pores increases with the chlorination temperature until 900 °C, followed by the significant decrease of both parameters at 1000 °C. Further analysis led to the conclusion that CDC obtained at 600 and 700 °C are ultramicroporous systems with slit pores having an average size of the order of 0.6 nm. CDC obtained at a high chlorination temperature have pores with sizes between 1 and 3 nm that are of the same size as the walls between the pores. A first comparison demonstrates that the stored energy E max is directly proportional to the anisometry of the pores embodied in the ratio l c / l p obtained by SAXS. Graphical abstract: Image 1